MHC class II presentation of FVIII-AnnexinA5 fusion proteins internalized by antigen presenting cells - Miranda, Mariarosaria; Leoni, Michela; van der Zwaan, Carmen; van Bruggen, Robin; Reutelingsperger, Chris P. M.; Fijnvandraat, Karin; Hoogendijk, Arie J.; van den Biggelaar, Maartje; Voorberg, Jan (Frontiers in Immunology, 2025)
IntroductionThe development of neutralizing antibodies (inhibitors) against coagulation factor VIII (FVIII) remains the most serious complication in the treatment of hemophilia A. While immune tolerance induction (ITI) is the standard strategy to eliminate these antibodies, it fails in approximately 30% of patients with severe hemophilia A, underscoring the need for innovative approaches to promote FVIII-specific tolerance.MethodsTo address this challenge, we generated fusion proteins composed of A2, A3-C1-C2 (light chain, LCh), and C2 domains of FVIII linked to Annexin A5 (AnxA5), a protein that binds phosphatidylserine (PS), a hallmark of apoptotic cells.ResultsELISA confirmed high-affinity binding of all fusion proteins to immobilized PS. To model PS exposure in vitro, red blood cells (RBCs) were treated with phorbol 12-myristate 13-acetate (PMA), leading to the release of PS-exposing microvesicles. Flow cytometry showed that FVIII-AnxA5 fusion proteins selectively bound to PS-exposing microvesicles but not to intact RBCs. Using mass spectrometry-based immunopeptidomics, we demonstrated that macrophages pulsed with FVIII-AnxA5 fusion proteins efficiently processed and presented FVIII-derived peptides on HLA-DR molecules.ConclusionsThese findings suggest that FVIII-AnxA5 fusion proteins can engage apoptotic cell clearance pathways to facilitate antigen presentation in a potentially tolerogenic context. This strategy may offer a novel means of inducing immune tolerance to FVIII in hemophilia A.